Synthesis and biological evaluation of a novel photo-activated histone deacetylase inhibitor. Issue 16 (15th August 2020) - Sama, Gopal R.; Liu, Hongbin; Mountford, Simon; Thompson, Phillip; Robinson, Andrea; Dear, Anthony E.
Graphical abstract: Abstract: Hydroxamic acid-based histone deacetylase inhibitors (HDACi) are a class of epigenetic agents with potentially broad therapeutic application to several disease states including post angioplasty mediated neointimal hyperplasia (NIH). Precise spatiotemporal control over the release of HDACi at the target blood vessel site is required for the safe and successful therapeutic use of HDACi in the setting of drug eluting balloon catheter (DEBc) angioplasty treatment of NIH. We aimed to develop and characterise a novel photoactive HDACi, as a potential coating agent for DEBc. Metacept-3 1 was caged with a photo-labile protecting group (PPG) to synthesise a novel UV365nm active HDACi, caged metacept-3 15 . Conversion of caged metacept-3 15 to active/native metacept-3 1 by UV365nm was achievable in significant quantities and at UV365nm power levels in the milliwatt (mW) range. In vitro evaluation of the biological activity of pre and post UV365nm activation of caged metacept-3 15 identified significant HDACi activity in samples exposed to short duration, mW range UV365nm. Toxicity studies performed in human umbilical vein endothelial cells (HUVEC's) identified significantly reduced toxicity of caged metacept-3 15 pre UV365nm exposure compared with native metacept-3 1 and paclitaxel (PTX). Taken together these findings identify a novel photo-activated HDACi, caged metacept-3 15, with pharmacokinetic activation characteristics and biological properties which may make it suitable for evaluation as a novel coating for targeted DEBc angioplasty interventions.